Módulos volumétricos pré-fabricados: avaliação da funcionalidade de leiautes residenciais - Artico, Rafael (Universidade do Vale do Rio dos Sinos, 2020)
This research presents the Volumetric Modular Architecture, which consists of the production of volumetric modules standardized in the industry, in a controlled environment, and are later transported and installed on the construction site. The building is formed through the association between these volumetric blocks, on a foundation prepared simultaneously to the production of modules in the industry, reducing the construction time. The element produced in the industry, in this research called Prefabricated Volumetric Module (MVP), must have measures appropriate to various possibilities of use, and association to the available construction materials, besides allowing road transport. The objective of this research is to analyze the functional behavior of these modules in the case of using them in residential buildings. Three modules of different measures were tested, designed according to the Modular Coordination Standards and limits for road transport, and evaluated according to the functionality requirements in the Performance Standard. The methodology used was the Design Science Research, which guides the development of artifacts and prescriptive conclusions. The artifacts developed by the research were the MVPs of three different dimensions as well as the layouts, which consist of associations of these modules, forming residential units, furnished apartments according to the Performance Standard. The layouts tested were 1, 2 and 3 bedrooms, with 3 relative positions in relation to the reference floor plan, resulting in layouts with 1, 2 or 3 facades exposed to the outside. The results of this research showed that the three dimensional possibilities of modules are valid for the development of this product, with advantage for the MVP300, with 3m x 3m x 3m x 3m, capable of complying with functional rules, besides the fact of allowing more flexibility to spaces, with the onus of wasting areas. The smallest modules (MVP260) is best suited to lean layouts, but it has limitations to compliance with the standard in some cases, while MVP280 module has intermediate characteristics, with some flexibility, but a little idle area.
Keywords: Arquitetura modular volumétrica; Projeto arquitetônico; Norma de desempenho; Coordenação modular; Volumetric modular architecture; Architectural design; Performance standard; Modular coordination; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo